Exploring Needs and Challenges in Learning English for Students of Economic Purposes: a case of 2nd year master economic students of The Djilali Bounaama Khemis Mililana University (مجلة الواحات للبحوث والدراسات, 2026)
This study explores the key challenges facing the  learning of English for Specific Purposes (ESP) in Algerian universities, with a particular focus on the Faculty of Economic Sciences, Commerce, and Management at Djillali Bounaama University of Khemis Miliana. Based on data collected through classroom observations and questionnaires administered to 100 Master’s students, the research highlights several critical issues hindering effective ESP instruction. These include the absence of a clearly defined ESP syllabus, lack of teacher training, insufficient teaching materials, limited instructional hours, large class sizes, and low student motivation. Additionally, the study emphasizes the growing importance of ESP in the academic and professional development of economics students, who require domain-specific vocabulary and skills. The findings underline the urgent need for targeted curriculum design, teacher support, and increased institutional collaboration to enhance ESP delivery and meet the specific language needs of learners.